Tuning Internal Accessibility via Nanochannel Orientation of Mesoporous Carbon Spheres for High-Rate Potassium-Ion Storage in Hybrid Supercapacitors - Park, Jongyoon; Kim, Kangseok; Lim, Eunho; Hwang, Jongkook (Advanced Functional Materials, 2025)
Enhancing the accessibility and utilization of active sites through mesopores in carbon anode materials is crucial for developing high-power potassium-ion hybrid supercapacitors (PIHCs). Here, a multiscale phase separation method combining block copolymer (BCP) microphase- and homopolymer (HP) macrophase-separation is utilized to produce two model carbon materials with controlled mesopore orientation: open-end (oe-MCS) and closed-end mesoporous carbon sphere (ce-MCS). BCPs form identical cylindrical micelles, and HPs encapsulate these cylindrical micelles within spheres and control their orientations relative to the interface. This approach manipulates only the degree of mesopore openings in the MCS materials while maintaining all other factors at similar levels. Opening mesopores in carbon anode materials primarily enhances K+ adsorption capacity, reduces K+ diffusion length, and improves ion transport. Thus, oe-MCS anode exhibits a higher specific capacity with a significant capacitive-controlled contribution. The resulting PIHC device displays maximum energy and power densities of 103 Wh kg−1 and 12 300 W kg−1, respectively, along with capacity retention of 86.1% after 20 000 cycles at 2.0 A g−1. This study significantly advances the understanding of mesopore design to improve capacitive K+ storage in hard carbon materials, paving the way for the development of high-power PIHCs.
Keywords: Carbon Spheres; High-power-density; Hybrid supercapacitors; Mesopore; Mesopore orientation; Mesoporous carbon; Mesoporous carbon sphere; Multiscale phase separation; Potassium ions; Potassium-ion hybrid supercapacitor; high power density; mesopore orientation; mesoporous carbon sphere; multiscale phase separation; potassium-ion hybrid supercapacitor